Human capital: definition, characteristics, reproduction - Kompaniets, V. V. (Science and Transport Progress, 2008)
In the article the research of category «human capital» is conducted: the difference in approaches to interpretation of human capital is determined; the features of human capital are generalized and systematized; the process of its reproduction is explored.